Pohybová soustava - svaly dolních končetin, jejich posilování, testování a prevence úrazu - strečink - Šimková, Veronika (2006)
Tittle of dissertation : Exercise system muscles of legs, their strengthen, testing and preventive ijuries - strecink Name of author : Veronika Šimková Number of pages : 60 Place of Publishing: Brno Year of publishing : 2006 In this bachelor thesis we have listed the most relevant dates concerning the most efficient excercises, stretching and testing of the muscles of legs. Key words : Muscles, leg, strengthen, stretching, testing.